(untitled) (International relations and international law Journal, 2016)
Kazakhstan has been focusing on the energy diplomacy with China more than Russia or the Western nations. China has been successful in terms of their access to secure the energy security through economic relations without stimulating the U.S. or Russia for advancing to the Central Asian region. But traditionally as for the region that Chinese began to influence economically, there were cases in which commercial supremacy were frequently gained by the overseas Chinese. The regions where the current overseas Chinese cannot economically influence are such developed nations as the Europe, the U.S., and Japan and as for the cases of such developing nations as the East-Asia, the overseas Chinese who cover about 10% of the entire population dominate more than 50% of local economy for the most part. Accordingly, if the expansion of the economical relations between Kazakhstan and China causes the immigration of the overseas Chinese in the future, it is presumed that similar situations will also occur in Kazakhstan like South East Asia, because Chinese immigration is a part of Chinese foreign policy to get energy security.